Speech of Mr. C.N. Smith, M.P.P. (Sault Ste. Marie), during the debate on the bill guaranteeing a loan of $2,000,000 to secure completion of the Algoma Central Railway and the revival of the allied industries at Sault Ste. Marie [electronic resource] : delivered in the Ontario Legislature Monday [i.e. Wednesday], April 13th, 1904. - Smith, Charles Napier, b. 1866. ([Toronto? : s.n., 1904)
Caption title. Electronic reproduction. Mode of access: Internet. 44